Computed Tomography Colonography (CTC): Is It Really the Non-Invasive Option We Think It Is? A Patient Experience Study. (August 2022) - Dewar, Greg; Brockbank, Bethany; Randall, Jonathan
Aims: Computed tomography colonography (CTC) is seen as a more tolerable alternative to colonoscopy, but patients struggle with the steps required for optimal diagnostic imaging. This prospective study aims to understand the experience of patients undergoing CTC.Methods: A survey was completed by a convenience sample of patients before and after CTC over 7 months. The 13-item questionnaire covered pre-test information, overall and specific experience of the test. The responses were tabulated and analyzed using descriptive statistics. Qualitative free-text responses were coded for content and thematic analysis.Results: At a response rate of 51%, surveys were received from 41 patients. Overall, most patients (54%) found the investigation better than expected. However, 18% stated they were not informed of potential side effects. Side effects were experienced by 49% of patients, including diarrhea (34%) and abdominal pain (24%). About 59% experienced discomfort with gas insufflation, and 86% found turning during the investigation difficult.Conclusion: A significant proportion of patients undergoing CTC experience side effects and difficulties completing the investigation. Patient information is important to improve patient experience of CTC.